Phenotypes of GNAO1 Variants in a Chinese Cohort - Yang, Xiaoling; Niu, Xueyang; Yang, Ying; Cheng, Miaomiao; Zhang, Jing; Chen, Jiaoyang; Yang, Zhixian; Zhang, Yuehua (Frontiers in Neurology, 2021)
This study aimed to analyze the genotypes and phenotypes of GNAO1 variants in a Chinese cohort. Seven male and 4 female patients with GNAO1 variants were enrolled, including siblings of brothers. Ten different GNAO1 variants (9 missense and 1 splicing-site) were identified, among which 6 were novel. All the variants were confirmed to be de novo in peripheral blood DNA. Eight (73%, 8/11) patients had epilepsy; the seizure onset age ranged from 6 hours after birth to 4 months (median age, 2.5 months). Focal seizures were observed in all 8 patients, epileptic spasms occurred in 6 (75%, 6/8), tonic spasm in 4 (50%, 4/8), tonic seizures in 2, atypical absence in one, and generalized tonic-clonic seizures in one. Seven patients had multiple seizure types. Eight (73%, 8/11) patients had movement disorders, 7 of them having only dystonia, and one having dytonia with choreoathetosis. Varying degrees of developmental delay (DD) were present in all 11 patients. The phenotypes were diagnosed as early infantile epileptic encephalopathy (EIEE) in 2 (18%) patients, which were further diagnosed as West syndrome. Movement disorders (MD) with developmental delay were diagnosed in 2 (18%) brothers. EIEE and MD were overlapped in 6 (55%) patients, among which 2 were diagnosed with West syndrome, 1 with Ohtahara syndrome, and other 3 with non-specific EIEE. One (9%) patient was diagnosed as DD alone. The onset age of GNAO1-related disorders was early infancy. The phenotypic spectrum of GNAO1 included EIEE, MD with DD, and DD alone.